2016
DOI: 10.1021/acs.jpcc.6b03923
|View full text |Cite
|
Sign up to set email alerts
|

Chirality Specific Triplet Exciton Dynamics in Highly Enriched (6,5) and (7,5) Carbon Nanotube Networks

Abstract: Single-walled carbon nanotubes (SWNTs) show high aspect ratio, thermal and chemical stability as well as charge mobility, and therefore appear ideally suited for improving charge extraction in organic photovoltaic (OPV) devices. Since typical charge extraction times in OPV devices are in the microsecond range, the interplay of the desired charged states with long-lived neutral states in SWNTs such as triplet excitons becomes important. Triplet excitons have recently been investigated in (6,5) SWNTs with an opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 50 publications
0
14
1
Order By: Relevance
“…Charges or triplets, for example, are reported to live for nanoseconds. [ 38 ] Figure 3b,e depicts that the amplitude of the PAnormals and PAnormalc in the OPV48:PCBM sample with SWNTs are larger, while the amplitude of PB is lower, and they decay faster (see also Figure S5, Supporting Information). The variation of pump intensity did not result in any significant difference in the PAnormals amplitude w/o SWNTs (see Figure S6, Supporting Information), but with SWNTs the decay of PAnormalc slowed down slightly at high pump intensity (see Figure S7, S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Charges or triplets, for example, are reported to live for nanoseconds. [ 38 ] Figure 3b,e depicts that the amplitude of the PAnormals and PAnormalc in the OPV48:PCBM sample with SWNTs are larger, while the amplitude of PB is lower, and they decay faster (see also Figure S5, Supporting Information). The variation of pump intensity did not result in any significant difference in the PAnormals amplitude w/o SWNTs (see Figure S6, Supporting Information), but with SWNTs the decay of PAnormalc slowed down slightly at high pump intensity (see Figure S7, S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…However, we have previously reported that when a sample contains mixed chiralities, substantial photoexcitation transfer occurs from larger bandgap tube to lower bandgap tube within 100 ps in pure SWNTs samples (without a donor or acceptor material). [ 38 ] Nonetheless, since we pumped our sample at 532 nm (relevant to the solar cells), the photoexcited‐state dynamics in our sample is very much dominated by the charge dynamics of the polymer:PCBM blends.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations